PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBASIS EKSPERIMEN TERHADAP MOTIVASI DAN HASIL BELAJAR IPAS SISWA KELAS IV SEKOLAH - Silalahi, Eka Kartika; Simbolon, Dedi Holden (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the need for science and social studies learning that can improve students’ learning motivation and learning outcomes through active, concrete, and experience-based learning activities. This study aimed to examine the effect of an experiment-based guided inquiry learning model on fourth-grade elementary students’ learning motivation and science and social studies learning outcomes. A quantitative approach with a quasi-experimental method and a pretest-posttest control group design was employed. The sample consisted of 43 students, including 22 students in the experimental class and 21 students in the control class. The experimental class was taught using the experiment-based guided inquiry learning model, while the control class received conventional instruction. The research instruments included a science and social studies achievement test, a learning motivation questionnaire, and a learning implementation observation sheet. The data were analyzed using descriptive statistics, normality tests, homogeneity tests, and independent samples t-tests. The results showed that the average learning motivation score of the experimental class was 90.15%, which was higher than that of the control class at 72.22%. The average posttest score of the experimental class was 86.00, while the control class obtained 76.24. The hypothesis testing results showed a significance value of less than 0.05, indicating a significant difference between the experimental and control classes. Therefore, the experiment-based guided inquiry learning model had a positive effect on fourth-grade students’ learning motivation and science and social studies learning outcomes. This model can be used as an alternative strategy for active, engaging, and student-centered science and social studies learning in elementary schools.